Muscular atrophy, impaired epithelial autophagy and UCHL1 increase in androgen-deficient cauda epididymis - de Santi, Fabiane; Lunardi, Isadora Dantas [UNESP]; Beltrame, Flávia Luciana; Cerri, Paulo Sérgio [UNESP]; Sasso-Cerri, Estela [UNESP] (Oxford University Press (OUP), 2020)
In epididymis, cimetidine induces androgenic failure due to reduced sex hormone-binding globulin stromal levels and blockade of androgen receptor (AR) nuclear import. UCHL1, a hydrolase of ubiquitin-proteasome system (UPS), seems to play a role in autophagy and apoptotic pathway. However, the role of UPS and autophagy in epididymis has not been clarified. We evaluated UCHL1 and autophagy in epididymal cauda epithelium under androgenic deficiency induced by cimetidine, focusing on the interplay among these processes and apoptosis. The integrity of epididymal muscular layer was also evaluated. Male rats received cimetidine (CMTG) or saline (CG). Seminal vesicles were weighed, the expression of androgen-responsive genes Crisp1 and connexin 43 (Cx43) in cauda epididymis was evaluated, and cauda fragments were processed for light and transmission electron microscopy. The epithelium height and muscular thickness were measured. TUNEL, immunohistochemistry for caspase-3 and Cx43, and immunofluorescence for AR, Bcl-2, UCHL1, MAP LC3A, and p62/SQSTM1 (autophagic markers) were performed. Bcl-2, UCHL1, and Cx43 were detected by Western blot. In CMTG, the reduction in seminal vesicles weight accompanied by downregulation of Crisp1 and Cx43 confirmed epididymal androgenic failure. These results were associated with muscular atrophy, apoptosis and weak Cx43 and AR immunoexpression, supporting the androgenic dependence of muscular integrity. The high UCHL1 levels and reduction in Bcl-2 reinforce UCHL1 role in epithelial cells death. The intense immunoexpression of LC3A and p62/SQSTM1 indicates autophagic disturb, which in association with high UCHL1 levels, points to a role of UPS and autophagy in the regulation of epididymal epithelial cells viability under androgenic control.